Evaluation of Network Function Virtualization Efficiency in Network Traffic Management - Rusdan, Muchamad; Hendayun, Mokhamad; Kuswayati, Sri (PPM Telkom University, 2025)
This study investigates the efficiency of Network Function Virtualization (NFV) in managing network traffic using a simulation-based experimental approach. NFV offers flexibility, scalability, and cost-efficiency by replacing hardware-based functions with software-based services. The research involves the deployment of Virtual Network Functions (VNFs) such as firewalls, load balancers, and intrusion detection systems within a simulated environment using tools like Mininet, OpenStack, and GNS3. Performance was evaluated under varying traffic conditions—normal, moderate, and high load scenarios—by measuring latency, throughput, jitter, CPU, and memory usage. The findings indicate that while NFV performs comparably to traditional systems under low to moderate load, it suffers from performance degradation under high traffic, particularly in latency and resource utilization. However, the integration of intelligent orchestration and dynamic resource management can mitigate these limitations. The results suggest that with proper optimization, NFV can serve as a viable alternative to traditional network infrastructure, especially in supporting next-generation network applications. This study contributes to the understanding of NFV’s operational performance and provides recommendations for its deployment in modern networks.